Strategi Kementerian Sekretariat Negara dalam Mewujudkan Birokrasi Efektif dan Responsif melalui Reformasi Administrasi Negara - Delviyanti, Diva Tri Delviyanti; Syamsir; Afifah Afra Amatullah; Tasya Rudinia Berty; Syaifa Azurra Hamid (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study analyzes the strategies of the Ministry of State Secretariat of the Republic of Indonesia in realizing an effective and responsive bureaucracy through state administrative reform. The purpose of this study is to examine the implementation of bureaucratic reform policies and their impact on institutional performance and governance. The research employs a descriptive qualitative approach using secondary data obtained from official government documents, laws and regulations, institutional performance reports, and relevant scientific literature. Data collection techniques were conducted through documentation study and literature review, focusing on policy documents and academic sources related to state administrative and bureaucratic reform. Data analysis techniques were carried out using qualitative descriptive analysis through the stages of data reduction, data presentation, and conclusion drawing, supported by source triangulation to ensure data validity. The results indicate that state administrative reform strategies at the Ministry of State Secretariat focus on simplifying bureaucratic structures, enhancing the competence of civil servants, utilizing information technology, and strengthening performance accountability systems. The implementation of these strategies has contributed to improving administrative efficiency, accelerating decision-making processes, and enhancing bureaucratic responsiveness to governmental needs.